Implementasi Games Pembelajaran â€œFelix and the Virology Zoneâ€ Berbasis RPG Maker MV pada Pembelajaran Biologi terhadap Keterampilan Proses Sains - Muhamad Kurnia Sugandi; Abdur Rasyid (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2020)
The learning process of biology hasnâ€™t led to direct observation of the object to be studied, this has an impact on the development of students' science process skills which cannot be oriented properly to the learning process of biology. The purpose of this study was to determine the application of the android version of RPG Maker MV based learning games to improve science process skills on the concept of viruses. The research method used Quasi-Experimental Design with Nonequivalent Control Group Pretest-Postest. The results showed the value of Sig. (2-tailed) of 0.000 <0.05, student responses> 50%, the rest answered strongly agree. So it can be concluded that, there is a significant difference in effectiveness between the implementation of the android version of the RPG Maker MV based learning game